Efficacy and safety of bendamustine for the treatment of patients with recurring Hodgkin lymphoma. (20th November 2012) - Corazzelli, Gaetano; Angrilli, Francesco; D'Arco, Alfonso; Ferrara, Felicetto; Musto, Pellegrino; Guarini, Attilio; Cox, Maria Christina; Stelitano, Caterina; Storti, Sergio; Iannitto, Emilio; Falorio, Simona; Califano, Catello; et al.
Summary The management of patients with Hodgkin lymphoma (HL) recurring after stem cell transplantation (SCT) and multiply relapsed disease remains challenging. We report on 41 such patients who received bendamustine hydrochloride, a bifunctional mechlorethamine derivative mechanistically unrelated to traditional alkylators, after a median of four prior chemotherapy lines, including SCT in 85% of cases. Bendamustine was given at doses of 90–120 mg/m2 every 21 or 28 d. At first assessment (2–4 cycles), the overall response rate (ORR) was 78% with 12 (29%) complete (CR) and 20 (49%) partial responses (PR). Upon treatment prolongation to 6–8 courses, 40% of PRs progressed, yielding a final ORR of 58% with 31% of CRs. Eight patients (two CRs, six PRs) were subsequently allotransplanted. Median progression‐free and overall survival exceeded 11 and 21 months respectively; complete responders displayed a median disease‐free survival above 9 months with a relapse rate of only 30%. Outcomes were independent of disease chemosensitivity, previous transplant and bendamustine dose‐intensity. No life‐threatening or unexpected adverse events occurred. Within the limits of a retrospective analysis and schedule heterogeneity, these results appear very encouraging and prompt prospective trials to confirm bendamustine as a valuable option in the palliative setting and in cytoreductive strategies before allotransplantation.